Gestión de los inventarios en las compañías que se dedican a la venta al por mayor y menor de materiales de construcción - Pulla Morocho, Carmen Angélica (2020)
The purpose of this research project is to suggest an inventory management model for the financial decision-making of the company DISTRANORT S.A., in order to carry out a timely inventory management; in this way it will be possible to optimize costs in all operational, administrative, accounting and financial processes. The import of inventory control and management in this type of business should be emphasized as it is a sector not so easy to control and monitor since its market varies constantly, which is intended to maintain an inventory control and order by continuing with the accounting and financial area….........